Attentional capture by incongruent object/background scenes in patients with Alzheimer disease. (October 2018) - Lenoble, Quentin; Corveleyn, Xavier; Szaffarczyk, Sébastien; Pasquier, Florence; Boucart, Muriel
Abstract: Aim: Object/background association is critical to understand the context of visual scenes but also in daily life tasks like object search. Patients with Alzheimer disease (AD) exhibit impairment in scene processing at different levels: perception, recognition, memory and spatial navigation. We explored whether patients with AD make use of contextual information in congruent and incongruent target/background conditions in three different saccadic choice tasks. Experiment: We recruited 36 participants (12 young, 12 patients with AD at a moderate stage and 12 age-matched controls). Pairs of scenes (one congruent and one incongruent object/background) were displayed. In a free viewing task we recorded whether the participants spontaneously direct their gaze (eye tracker recordings) toward the congruent or the incongruent scene. In a task referred as "implicit", the participants had to saccade toward a pre-defined target (animal or piece of furniture) in a scene (congruent or not with the target). In a task, called "explicit", participants had to saccade towards the congruent scene. Results: In contrast with both young and older controls patients with AD showed difficulties to refrain a first saccade toward incongruent scenes in the free viewing and the implicit tasks. They were at chance level in the explicit task. When given time to explore the two scenes, in a manual response condition, they were able to accomplish the implicit and explicit tasks with good accuracy. Conclusion: In contrast to healthy controls patients with AD exhibited a strong, significant, bias towards incongruent object/background scenes, even in the free viewing task, suggesting that unfamiliar or deviant stimuli attract their attention spontaneously. This result is in line with studies showing impairments in filtering out irrelevant distractors in visual search tasks and with studies suggesting inefficient top-down control to select relevant information at early stage of the disease.